APPLICATION OF THE TREND MOMENT METHOD FOR FORECAST SALES OF SONGKET FABRIC PRODUCTS AT UD. MANDIRI PERKASA - Maulana, Fajar; Rahmi, Elvika; Sari, Ika Yusnita (INFOKUM, 2022)
Forecasting is a process for determining how much demand will exist as soon as the order is placed. It includes determining how much demand will exist in terms of quantity, quality, time, and location in order to fulfill the order for the goods. Peramalan is a strategy for predicting or predicating impending events, usually with the help of an earlier-than-expected deadline for submitting a request for proposals. This request is then based on the company's resources and existing capabilities for submitting requests, or other factors. According to songket results that are currently located in Padang, UD Mandiri Perkasa is a business that specializes in the trade of songket ink. UD Mandiri Perkasa is currently experiencing challenges from both a consumer-focused perspective as well as from the type of goods it is currently supplying. With the use of peramalan, it is possible to determine how much money should be spent on a certain product and to minimize waste. A forecast for the next single month will be made in this essay.